2019
DOI: 10.1021/acs.nanolett.9b01660
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli-Responsive Polymer–Prodrug Hybrid Nanoplatform for Multistage siRNA Delivery and Combination Cancer Therapy

Abstract: Nanoparticles (NPs) formulated with cationic lipids and/or polymers have shown substantial potential for systemic delivery of RNA therapeutics such as small interfering RNA (siRNA) for the treatment of cancer and other diseases. While both cationic lipids and polymers have demonstrated the promise to facilitate siRNA encapsulation and endosomal escape, they could also hamper cytosolic siRNA release due to charge interaction and induce potential toxicities. Herein, a unique polymer−prodrug hybrid NP platform wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
92
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 70 publications
2
92
0
Order By: Relevance
“…Using prodrugs is a promising approach to enhance the selectivity and efficacy of chemotherapeutic drugs. Having this in mind, an amphiphilic cationic prodrug based on lipids was employed to load RNA therapeutics for co-delivery ( Figure 9 ) [ 194 ]. The amphiphilic lipids formed nanoparticles in aqueous conditions and simultaneously encapsulated siRNA with an entrapment efficiency of about 35.1–68.9% (for different nanoparticles).…”
Section: Nano-vehiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using prodrugs is a promising approach to enhance the selectivity and efficacy of chemotherapeutic drugs. Having this in mind, an amphiphilic cationic prodrug based on lipids was employed to load RNA therapeutics for co-delivery ( Figure 9 ) [ 194 ]. The amphiphilic lipids formed nanoparticles in aqueous conditions and simultaneously encapsulated siRNA with an entrapment efficiency of about 35.1–68.9% (for different nanoparticles).…”
Section: Nano-vehiclesmentioning
confidence: 99%
“…The findings showed that esterase (as overexpressed in the tumor microenvironment) led to cleavage of the prodrug, allowing the siRNA and anticancer drug to be efficiently liberated in the cytoplasm. These types of nanocarriers showed about 70% knockdown in the expression of PLK1 [ 194 ].…”
Section: Nano-vehiclesmentioning
confidence: 99%
“…As the major tumor feature, various nanomaterials including polymer (Kato et al, 2013;He et al, 2016;Xu et al, 2017;Zhao et al, 2017;Shen et al, 2018;Saw et al, 2019), silica and upconversion (Qiao et al, 2017) nanoparticles were designed for smart drug delivery via pH-response. With excellent pH-responsive features (e.g., via structural or solubility change), polymer-based nano-platforms demonstrate a great advantage in pH-triggered drug release (Kocak et al, 2017).…”
Section: Ph-responsive Nanomedicinementioning
confidence: 99%
“…By coating with pH-sensitive mPEG-b-PDPA 20 , succinobucol (SCB), vascular cell adhesion molecule-1 (VCAM-1) inhibitor could efficiently escape from micelles (PWMs) at TME, and inhibit the lung metastasis of breast cancer tumors for around ∼6.25 and 4.5 times, respectively, in comparison with saline and SCB groups . Besides, by combing enzymeinduced feature (esterase), Saw et al successfully synthesized an N15 polymer nanoparticle (<100 nm) consisting of a core (siRNA and amphiphilic cationic mitoxantrone, MTO) and pH-responsive PEG shell (Saw et al, 2019) (Figure 1A). The siRNA of Polo-like kinase 1 (PLK1) (more than 90%) would be only released after a two-step decomposition caused by acidic pH and esterase in the tumor area, which efficiently inhibited ∼70% of PLK1 expression and around 2-fold of MDA-MB-231 tumor growth within 18 days (Figure 1B).…”
Section: Ph-responsive Nanomedicinementioning
confidence: 99%
“…A widely-used integration strategy is based on various material synthesis methods, designing the nanoparticles as a core-shell structure to co-load two therapeutic agents 7 , 8 , and introducing multiple functional molecules, such as polyethylene glycol (PEG) 9 , 10 , targeting ligands 11 , 12 and cationic charges 13 , 14 , to maximize its delivery efficiency. Moreover, some stimuli-responsive 15 - 18 or multistage nanosystems 19 - 22 have tried to integrate the functions of various materials, with all components working in a coordinated way, thus enabling them as nanomedicines with high combination therapeutic efficacy. Although these are fantastic works, more efforts have to be dedicated to explore a high-performance and clinically available nanoplatform capable of co-delivering drugs and nucleic acids, and with optimized or additional properties.…”
Section: Introductionmentioning
confidence: 99%